Durable purchases and consumer decision-making - Nabi, Kamalun; Raut, Kishore C. (Delhi : Academic Excellence, 2008)
Contributed articles published to commemorate a festschrift of Prof. M.S. Venkataramani (1925-2006).
Includes bibliographical references and index.
Keywords: Consumer behavior; Marketing -- Management